Impact of the SVLK Policy Post UUCK on the Sustainability of Community Forests in Banten Province, Indonesia - Tutik Handayani; Bramasto Nugroho; Leti Sundawati (Postgraduate, University of Mataram, 2026)
The Timber Legality Verification System (SVLK) is a policy instrument designed to ensure the legality of timber forest products and sustainability of community forest management in Indonesia. This study aims to analyze the implementation of the SVLK policy in Banten Province, map the roles and interests of stakeholder, and assess its economic impact on the income of community forest farmers before and post implementation of the Job Creation Law (UUCK). The study used a mixed method approach (combining qualitative and quantitative) using structured and in-depth interviews to farmers and related stakeholders. The analysis used consist of policy implementation analysis, stakeholder analysis (actor grid), income analysis, and the Revenue Cost Ratio (R/C) analysis. The results indicate that SVLK implementation has not been effective due to limitations in human resources, budget, policy communication, and the absence of specific SOPs. The Forest Management Unit (FMU) is a forest farmer association formed with a common goal and has a management, which will undergo SVLK certification in Banten Province. The FMU and the Ministry of Forestry play the role of Key Players with the highest level of interest and influence. Economically, self-funded SVLK certification causes losses for farmers, while financial facilitation from the state budget (APBN) improves business feasibility but has not significantly improved farmer welfare. This study recommends improvements to the SVLK policy design through strengthening institutional capacity, regulatory consistency, and fairer economic incentive schemes for community forest farmers.